The Islamic-Christian Conflict In Northern Andalusia During The Reign Of Caliph Abd Al-Rahman Al-Nasser III (Journal of Namibian Studies : History Politics Culture, 2023)
This research discussed the most important battles and events that occurred during the reign of Caliph Abd al-Rahman al-Nasir III. It used the qualitative method of reading and analyzing historical texts as a tool for collecting data. Braun and Clark's (2006) thematic approach serves as the analytical tool for data. The findings of the study were (i) Caliph Al-Nasser pursued a policy of quelling internal revolts in preparation for the defense of Andalusia., (ii) The intelligence strategy employed by Caliph Al-Nasser played a significant role in achieving victory , (iii), The Caliph failed to meet the expectations of the Arab soldiers by appointing a non-Arab commander for the Battle of the Trench, which resulted in the soldiers' discontent, (iv) During the Battle of the Trench, most of the soldiers did not accept the idea of their commander being a non-Arab, and this was one of the causes of the defeat that befell the Caliph's forces, (v) The Caliph's forces did not study the geography of the battle site before entering combat in the Battle of the Trench, and this led to their defeat in the battle, and (vi) the Caliph stands out as a notable figure in history, celebrated for his resolute commitment to realizing his objectives, particularly within the sphere of military pursuits.